Comparing the Importance of Curriculum Integration from the point of view of Academic Staff of Tabriz University of Medical Sciences and University of Tabriz Faculty Members - Firooz Mahmoodi; Zeynab Cheraghi (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: The rapid expansion of knowledge and information, fragmentation and dispersion of various sectors of traditional curricula, and little connection with the real world have made learners pay more attention to the issue of integration in curricula. The aim of this study was to compare the viewpoints of academic staff of Tabriz University of Medical Sciences with the University of Tabriz about integration steps. Materials and Methods: This study is descriptive -survey. The population of study were 650 academic staff employed at University of Tabriz and 324 members of the academic staff at the Tabriz University of Medical Sciences. The sample for the study was randomly selected, 242 academic staff from Tabriz University and 177 from Tabriz University of Medical Sciences based on Morag sampling Table. Data were collected using a researcher- made questionnaire. Data were analyzed by descriptive statistics (Mean and Standard deviation indicators) and inferential statistics (MANOVA) through SPSS 22. Results: MANOVA test Results showed that there was a big gap between the opinion of the academic staff of Tabriz University of Medical Sciences and the University of Tabriz on the steps of awareness, harmonization, nesting, multi-disciplinary and inter- disciplinary are a significant difference. The mean of academic staff of Tabriz University of Medical Sciences in the mentioned steps was greater than the mean of the University of Tabriz academic staff. Results, on the other hand, showed that the gap was not significant between the two regarding steps of isolation, temporal co-ordination, sharing, correlation, complementary program and trans-disciplinary. Conclusion: The results showed that the academic staff of Tabriz University of Medical Sciences paid more attention to the steps of awareness, harmonization, nesting, multi-disciplinary and inter- disciplinary than those of Tabriz University. Therefore, more attention should be paid to integration in medical curricula.